Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1051/0004-6361/201629440
|View full text |Cite
|
Sign up to set email alerts
|

Star formation and gas flows in the centre of the NUGA galaxy NGC 1808 observed with SINFONI

Abstract: NGC 1808 is a nearby barred spiral galaxy which hosts young stellar clusters in a patchy circumnuclear ring with a radius of ∼240 pc. In order to study the gaseous and stellar kinematics and the star formation properties of the clusters, we perform seeing-limited H + Kband near-infrared integral-field spectroscopy with SINFONI of the inner ∼600 pc. From the M BH − σ * relation, we find a black hole mass of a few 10 7 M. We estimate the age of the young stellar clusters in the circumnuclear ring to be 10 Myr. N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(67 citation statements)
references
References 144 publications
10
57
0
Order By: Relevance
“…Due to the proximity of the H 2 λ2.122 µm and the Brγ line in wavelength, the extinction correction here would only be of the order of a few percent which is much smaller than the error introduced by the uncertainties in the extinction estimate. Therefore we decide not to correct this line ratio (see discussion in Busch et al 2017).…”
Section: Gas Excitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the proximity of the H 2 λ2.122 µm and the Brγ line in wavelength, the extinction correction here would only be of the order of a few percent which is much smaller than the error introduced by the uncertainties in the extinction estimate. Therefore we decide not to correct this line ratio (see discussion in Busch et al 2017).…”
Section: Gas Excitationmentioning
confidence: 99%
“…The observations of these galaxies with integral-field spectroscopy in the near-infrared (NIR) are complementary to the millimeter data (e.g., NGC 1433NGC , 1566NGC , and 1808Smajić et al 2014Smajić et al , 2015Busch et al 2017). The NIR data reveal informa-Article number, page 1 of 20 arXiv:1901.06241v1 [astro-ph.GA] 18 Jan 2019 A&A proofs: manuscript no.…”
Section: Introductionmentioning
confidence: 97%
“…In particular, Na I D is seen blueshifted in absorption and redshifted in emission and B-R images show that the dust plumes associated with the outflow reach ∼3 kpc above the plane. Near-infrared integralfield spectroscopy with SINFONI by Busch et al (2017) showed a large gas reservoir and a disturbed gas velocity field that shows signs of inflowing streaming motion in the central ∼100 pc.…”
Section: Ngc 1808mentioning
confidence: 99%
“…If we separately fit to the lower-and higher-excitation lines, we derive temperatures of 1640 ± 470 K and 3330 ± 880 K, respectively. We can also compute the ro-vibrational temperatures from the ratios H 2 1-0 S(0)/H 2 1-0 S(2) and H 2 2-1 S(1)/H 2 1-0 S(1) (Busch et al 2017), and derive T rot(ν=1) = 530 K and T vib = 3870 K.…”
Section: Emission Line Properties and Diagnosticsmentioning
confidence: 99%